2002
DOI: 10.1038/sj.jp.7210694
|View full text |Cite
|
Sign up to set email alerts
|

Does Incomplete Growth and Development Predispose Teenagers to Preterm Delivery? A Template for Research

Abstract: Pregnant teenagers are in better physical condition, suffer from fewer chronic diseases, and engage in fewer health-risky behaviors than socioeconomically similar pregnant adults, but give birth to a disproportionately large number of preterm infants. This systematic review of the adolescent pregnancy literature defines the unique risks associated with being young and pregnant by examining how the physical and psychosocial changes that are characteristic of puberty and adolescence interact with traditional ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 107 publications
2
59
0
4
Order By: Relevance
“…7 Alternatively, the gynaecological immaturity of adolescents, which is characterised by a short uterine cervix and alkaline vaginal pH, may predispose them to an increased risk of subclinical lower genital infection, leading to an increased risk of preterm delivery. 26 The increased risk of perinatal death among infants born to adolescent mothers disappeared after further adjustment for sociodemographic characteristics, the number of antenatal care visits, and gestational age at birth. This finding supports the results of previous studies, which have concluded that the increased risk of neonatal mortality among adolescents is largely attributable to preterm birth and the socio-economic circumstances of younger mothers.…”
Section: Discussionmentioning
confidence: 99%
“…7 Alternatively, the gynaecological immaturity of adolescents, which is characterised by a short uterine cervix and alkaline vaginal pH, may predispose them to an increased risk of subclinical lower genital infection, leading to an increased risk of preterm delivery. 26 The increased risk of perinatal death among infants born to adolescent mothers disappeared after further adjustment for sociodemographic characteristics, the number of antenatal care visits, and gestational age at birth. This finding supports the results of previous studies, which have concluded that the increased risk of neonatal mortality among adolescents is largely attributable to preterm birth and the socio-economic circumstances of younger mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Younger maternal age is associated with being unmarried, primiparous and under-educated, alcohol/substance abuse, heavy smoking and inadequate prenatal care, which may lead to adverse pregnancy outcomes (2,(16)(17)(18)(19)(20)(21)(22). Young mothers may also be more likely to have a pregnancy due to sexual abuse compared with adult mothers, which could lead to an impaired stress response or to variable behaviors that increase the likelihood of preterm delivery (22).…”
Section: Discussionmentioning
confidence: 99%
“…Young mothers may also be more likely to have a pregnancy due to sexual abuse compared with adult mothers, which could lead to an impaired stress response or to variable behaviors that increase the likelihood of preterm delivery (22). To evaluate the effect of younger maternal age on pregnancy outcomes, these confounding variables have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for adverse pregnancy outcomes have been thought to be their biological immaturity or poor social, economic and behavioral factors such as smoking, alcohol/substance abuse, malnutrition and inadequate prenatal care (17-22). However, the previous studies had conflicting findings regarding whether the effect of young maternal age on adverse pregnancy outcomes were caused by their biological immaturity or poor social, economic and behavioral factors (17)(18)(19)(20)(21)(22). …”
mentioning
confidence: 99%